Dropping in and dropping out: experiences of sustaining and ceasing amateur participation in classical music. Issue 3 (20th June 2016) - Pitts, Stephanie E.; Robinson, Katharine
Abstract : The benefits of lifelong musical participation have been repeatedly demonstrated through research and anecdote, and yet the challenging question of why more people are not engaged in these activities is rarely addressed. This project used interviews with eighteen current and past amateur ensemble members to explore themes of social acceptance, musical satisfaction and confidence, and to consider how personal determination and circumstances affect adults' continuation of musical activities in the face of competing demands. By understanding how musical participation is viewed by those who no longer engage, or who have had long gaps in their engagement, the research aimed to reconsider the challenges of sustaining participation, and the perceived long-term effects of musical learning and experience. Conclusions are drawn about the role of music education in laying foundations for lifelong participation, and the benefits of providing all children with experience and understanding of making music.